A Torsion Relative Angle Measurement Method Based on Fiber-Loop Ring-Down with Intra-Cavity Amplification - Ma, Tao; Tian, Yongsheng; Liu, Shaohui; Ma, Jiahe; Liu, Heng; Wang, Fang; Zhou, Ziqiang (Micro and Nanosystems, 2022)
Background: The fiber-loop ring-down spectroscopy technique has the benefits of optical fiber sensors and also has many unique advantages. Combined with various sensor structures, the FLRD system can achieve different physical, chemical, and biological sensors. Objective: To find a way to solve the problems of light fluctuation and low sensitivity, high sensitivity, and reliability torsion relative angle measurement system is necessary. Methods: The torsion relative angle measurement is achieved by using the fiber loop ring-down intra- cavity amplification. The sensitivity, correlation coefficient, and repeatability are analyzed with the experiment. Results: The sensitivity and correlation coefficient of the proposed system are 4.05 μs/° and 0.9996, respectively. The repeated experiments show that the standard deviation is 9.592×10-4. Conclusion: The proposed measurement method provides a way to solve the problems of light fluctuation and low sensitivity and has promising applications in the optically active solutions, fiber radial stress birefringence and polarization state measurement of fiber lasers.
Keywords: intra-cavity amplification